EFEKTIFITAS KONSENTRASI DAN LAMA PERENDAMAN GIBERELIN TERHADAP PERKECAMBAHAN TIGA VARIETAS TRUE SHALLOT SEED - Hantari, Dimar; Wijayanti, Dinda Pangestika (Institute of Computer Science (IOCS), 2026)
This study aimed to determine the optimal gibberellin concentration and soaking duration to enhance the germination of three shallot varieties derived from True Shallot Seed (TSS). The research was conducted from October to November 2025 in Triyagan Village, Mojolaban District, Sukoharjo Regency, Central Java. A Randomized Complete Block Design (RCBD) was employed with three treatment factors: gibberellin concentration, soaking duration, and variety. Observed variables included germination percentage, germination speed, seedling height, root length, and number of leaves. The results indicated that the variety factor significantly influenced all observed variables. Gibberellin treatment independently had a significant effect on all variables except root length. Soaking duration significantly affected germination and seedling height. Furthermore, a significant interaction was observed between variety and gibberellin on seedling height and leaf number, as well as an interaction between gibberellin and soaking duration on germination percentage. The application of 150 ppm gibberellin with a 12-hour soaking duration proved to be the most effective combination for improving the TSS germination across the three shallot varieties.